พระพุทธศาสนากับการพัฒนาเพื่อความยั่งยืน - ประยุต, พระครูสารกิจประยุต (วารสารศรีล้านช้างปริทรรศน์, 2017)
บทความวิชาการเรื่องนี้ มีวัตถุประสงค์เพื่อศึกษาการใช้หลักคำสอนทางพระพุทธศาสนา คือการใช้หลักทางสายกลาง หรือมัชฌิมาปฏิปทาเพื่อนำมาปรับใช้ในการพัฒนาเพื่อความยั่งยืนคือด้านสิ่งแวดล้อม ทำให้มีมากขึ้นจากการใช้เทคโนโลยีที่เหมาะสมและอนุรักษ์ทรัพยากรพื้นฐานให้มั่นคง ด้านสังคม มีการจัดสรรความเท่าเทียมกันในการใช้ทรัพยากรที่เป็นตัวชี้วัดพื้นฐานที่เพียงพอและจำกัดจำนวนประชากร และด้านเศรษฐกิจ ที่ต้องเติบโตอย่างเหมาะสมไม่ทำลายสิ่งแวดล้อมและความสมดุลในระบบนิเวศเพราะถ้าเราไม่นำหลักของทางสายกลางมาปรับใช้ก็จะไม่เกิดความยั่งยืน เพราะจะมีอย่างใดอย่างหนึ่งเกิน หรือหย่อนเกินไป เช่น ถ้ามีการอนุรักษ์ทรัพยากรธรรมชาติมากเกินไปโดยไม่นำมาใช้ประโยชน์ก็จะกลายเป็นว่ามีของดีแต่ไม่นำมาใช้มันก็เสียเปล่า หรือถ้านำมาใช้มากเกินไปมุ่งเน้นแต่จะนำทรัพยากรธรรมชาติมาพัฒนาเศรษฐกิจ ก็จะทำให้เสียสมดุลไป ดังนั้นจึงมีความจำเป็นที่จะต้องนำหลักของทางสายกลางคือเป็นคำสอนของพระพุทธศาสนามาเป็นแนวทางในการพัฒนาเพื่อความยั่งยืนสืบไป The purposes of this academic article wase to study implementation of the Buddhist principle, Majjhima-patipada or the middle path, to sustainable development in several aspects. In the environmental aspect, it should be made abundant by the usage of proper technologies and the stable conservation of fundamental resources. In the social aspect, the utilization of resources as thefundamental indicator was allotted equally and sufficiently to certain people, and in theeconomic aspect, it should be appropriately grown in progress and the environment and ecological balance should not be destroyed. As seen, sustainability was unavailable if the Buddhist principle of the middle path was not utilized because there might be something excessively overwhelmed or reduced. For example, if natural resources were excessively conserved and not utilized, availability of unutilized natural resources was seen useless. In case natural resources were over-abundantly utilized with the target to increase the country’s economy, existing natural resources were inevitably unbalanced.So, it was very important to take the Buddhist principle of the middle path as the guideline for further sustainable development.